Understanding and applying biological resilience, from genes to ecosystems - Thorogood, Rose; Mustonen, Ville; Aleixo, Alexandre; Aphalo, Pedro J.; Asiegbu, Fred O.; Cabeza, Mar; Cairns, Johannes; Candolin, Ulrika; Cardoso, Pedro; Eronen, Jussi T.; Hällfors, Maria; Hovatta, Iiris; et al. (Springer Science and Business Media LLC, 2023)
The natural world is under unprecedented and accelerating pressure. Much work on understanding resilience to local and global environmental change has, so far, focussed on ecosystems. However, understanding a system’s behaviour requires knowledge of its component parts and their interactions. Here we call for increased efforts to understand ‘biological resilience’, or the processes that enable components across biological levels, from genes to communities, to resist or recover from perturbations. Although ecologists and evolutionary biologists have the tool-boxes to examine form and function, efforts to integrate this knowledge across biological levels and take advantage of big data (e.g. ecological and genomic) are only just beginning. We argue that combining eco-evolutionary knowledge with ecosystem-level concepts of resilience will provide the mechanistic basis necessary to improve management of human, natural and agricultural ecosystems, and outline some of the challenges in achieving an understanding of biological resilience.
Keywords: Biodiversity; ecology